2019
DOI: 10.2983/035.038.0110
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Triploid Mortalities of Eastern Oysters Crassostrea virginica in the Virginia Portion of the Chesapeake Bay

Abstract: Since 2012, aquacultured eastern oysters Crassostrea virginica have been reported by oyster farmers to display mortality approaching 30%, and in some cases 85%, in areas of the lower Chesapeake Bay, VA. Based on accounts from industry, this mortality has typically affected 1-y-old oysters between May and early July, and has tended to occur in triploid oysters, which represent the vast bulk of production in the area. During this period, samples submitted for pathology have not revealed the presence of major pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…For example, Wadsworth et al (2019) found higher cumulative mortality in triploid C. virginica than diploids across growing sites within the Gulf of Mexico; mortalities were associated with sudden drops in salinity (< 5 ppt) and high temperature (> 30°C). The presence of multiple stressors preceding mortality events is consistent with both Guévélou et al (2019) and Matt et al (2020), who have noted that C. virginica triploid mortalities observed within Chesapeake Bay, VA are not correlated with the presence of elevated seawater temperature alone. Instead, common farm stressors, including tumbling stress and desiccation, as well as hyposalinity have been shown to contribute to triploid mortality (Bodenstein, 2019;Bodenstein et al, 2021Bodenstein et al, , 2023.…”
Section: Triploid Oysters Display Higher Mortality Rates Within Multi...supporting
confidence: 79%
See 3 more Smart Citations
“…For example, Wadsworth et al (2019) found higher cumulative mortality in triploid C. virginica than diploids across growing sites within the Gulf of Mexico; mortalities were associated with sudden drops in salinity (< 5 ppt) and high temperature (> 30°C). The presence of multiple stressors preceding mortality events is consistent with both Guévélou et al (2019) and Matt et al (2020), who have noted that C. virginica triploid mortalities observed within Chesapeake Bay, VA are not correlated with the presence of elevated seawater temperature alone. Instead, common farm stressors, including tumbling stress and desiccation, as well as hyposalinity have been shown to contribute to triploid mortality (Bodenstein, 2019;Bodenstein et al, 2021Bodenstein et al, , 2023.…”
Section: Triploid Oysters Display Higher Mortality Rates Within Multi...supporting
confidence: 79%
“…However, field assessments of triploid and diploid oyster survivorship over the course of a growing cycle suggest that summer mortality is more complicated than would be expected from differences in thermal tolerance limits alone. Triploid C. gigas, C. virginica, and C. hongkongensis have been shown to exhibit lower (Gagnaire et al, 2006;Qin et al, 2019), higher (Bodenstein et al, 2021(Bodenstein et al, , 2023Guévélou et al, 2019;Houssin et al, 2019;Matt, 2018;Matt et al, 2020;Wadsworth, 2018;Wadsworth et al, 2019), and comparable (Dégremont et al, 2012;Ibarra et al, 2017) mortality rates when compared with diploids depending on the environmental conditions present. For example, Wadsworth et al (2019) found higher cumulative mortality in triploid C. virginica than diploids across growing sites within the Gulf of Mexico; mortalities were associated with sudden drops in salinity (< 5 ppt) and high temperature (> 30°C).…”
Section: Triploid Oysters Display Higher Mortality Rates Within Multi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Triploid C. gigas , C. virginica , and C. hongkongensis have been shown to exhibit lower (Gagnaire et al, 2006; Qin et al, 2019), higher (Bodenstein et al, 2021, 2023; Guévélou et al, 2019; Houssin et al, 2019; Matt, 2018; Matt et al, 2020; Wadsworth, 2018; Wadsworth et al, 2019), and comparable (Dégremont et al, 2012; Ibarra et al, 2017) mortality rates when compared with diploids depending on the environmental conditions present. For example Wadsworth et al (2019) found higher cumulative mortality in triploid C. virginica than diploids across growing sites within the Gulf of Mexico; mortalities were associated with sudden drops in salinity (<5 ppt) and high temperature (>30°C).…”
Section: Discussionmentioning
confidence: 99%